2017
DOI: 10.1051/0004-6361/201730914
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous multicolour optical and near-IR transit photometry of GJ 1214b with SOFIA

Abstract: Context. The benchmark exoplanet GJ 1214b is one of the best studied transiting planets in the transition zone between rocky Earth-sized planets and gas or ice giants. This class of super-Earth/mini-Neptune planets is unknown in our Solar System, yet is one of the most frequently detected classes of exoplanets. Understanding the transition from rocky to gaseous planets is a crucial step in the exploration of extrasolar planetary systems, in particular with regard to the potential habitability of this class of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 88 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…It has been shown that in theory SOFIA has some distinct advantages for extremely precise time-domain spectrophotometric observations at optical and IR wavelengths (Angerhausen 2010;Angerhausen et al 2010Angerhausen et al , 2014Angerhausen et al , 2017. SOFIA op-erates in important wavelength regions, where the planet's black-body temperature peaks and contrast ratios between the star and planet improve.…”
Section: Exoplanets With Sofiamentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that in theory SOFIA has some distinct advantages for extremely precise time-domain spectrophotometric observations at optical and IR wavelengths (Angerhausen 2010;Angerhausen et al 2010Angerhausen et al , 2014Angerhausen et al , 2017. SOFIA op-erates in important wavelength regions, where the planet's black-body temperature peaks and contrast ratios between the star and planet improve.…”
Section: Exoplanets With Sofiamentioning
confidence: 99%
“…and 3.05 µm 'water ice' bands -that are not observable from the ground. Again only parts of the full program were observed and are published in Angerhausen et al (2017) and summarized below.…”
Section: Accepted Proposals In Cycles 1-4mentioning
confidence: 99%
See 3 more Smart Citations